2019
DOI: 10.1002/jcp.27815
|View full text |Cite
|
Sign up to set email alerts
|

A novel long noncoding RNA AK016739 inhibits osteoblast differentiation and bone formation

Abstract: The incidence of postmenopausal osteoporosis research 50% in middle‐aged and older women, however, effects of existing therapy are not ideal. Emerging evidence have proved that long noncoding RNAs (lncRNAs) was correlated with multiple physiological and pathology processes including development, carcinogenesis, and osteogenesis. However, reports on lncRNAs regulating bone formation were relatively limited. In this study, we screened osteogenic lncRNAs through mRNA/lncRNA microarray combined with gene coexpress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 39 publications
1
35
0
Order By: Relevance
“…Using human whole transcriptome microarray, Zhang et al profiled the expression and analyzed the functional network of lncRNAs during osteogenic differentiation of human bone marrow mesenchymal stem cells (hBMSC), in which a total of 1408 lncRNAs with 623 lncRNAs downregulating and 785 lncRNAs significantly upregulating were detected along with osteogenic differentiation [12]. In this study, we screened osteogenic-related lncRNAs in our established preosteoblast cell line [13] by performing mRNA and lncRNA microarray in combination with KEGG analysis and PCC co-expression analysis [7]. Among them, AK045490 was one of lncRNAs that showed the most significant increment [7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using human whole transcriptome microarray, Zhang et al profiled the expression and analyzed the functional network of lncRNAs during osteogenic differentiation of human bone marrow mesenchymal stem cells (hBMSC), in which a total of 1408 lncRNAs with 623 lncRNAs downregulating and 785 lncRNAs significantly upregulating were detected along with osteogenic differentiation [12]. In this study, we screened osteogenic-related lncRNAs in our established preosteoblast cell line [13] by performing mRNA and lncRNA microarray in combination with KEGG analysis and PCC co-expression analysis [7]. Among them, AK045490 was one of lncRNAs that showed the most significant increment [7].…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we have screened osteogenic lncRNAs through mRNA/lncRNA microarray combined with gene co-expression analysis. We speculate that AK045490 might be one of the osteoblastic differentiation inhibiting lncRNAs [7]. To determine the expression level of AK045490, we established two osteoporotic mice models, age-related osteoporotic mice model (aging mice) and postmenopausal osteoporotic mice model (ovariectomized mice, OVX mice).…”
Section: Elevated Ak045490 Expression In Bone Was Accompanied By Detementioning
confidence: 99%
See 1 more Smart Citation
“…An increasing number of experiments have confirmed that lncRNAs can regulate osteoblast functions, such as differentiation and apoptosis 18,23,26,33 . Our previous research first identified a sensitive lncRNA, lncRNA ODSM, in osteoblasts in a MG unloading environment that could promote osteoblast differentiation 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated that lncRNAs are associated with osteoporosis and other bone diseases 17 . Inhibiting AK016739 expression in vivo promoted osteogenic gene expression and rescued calvarial bone formation in ovariectomy (OVX) mice 18 . LncRNAs are involved in osteoblast differentiation and apoptosis.…”
Section: Introductionmentioning
confidence: 99%